Comparison between sonographic features and fine needle aspiration cytology with histopathology in the diagnosis of solitary thyroid nodule - Debanu De; Susmita Dutta; Soham Tarafdar; Suvrendu S Kar; Utpalendu Das; Keya Basu; Pradip Mukhopadhyay; Sujoy Ghosh (Indian Journal of Endocrinology and Metabolism, 2020)
Background: High resolution ultrasonography (USG) is the first-line investigation in evaluation of euthyroid nodules. Thyroid imaging reporting and data system (TIRADS) is an USG-based risk stratification system for classifying thyroid nodules. Subjects with high-risk category of TIRADS undergo fine needle aspiration cytology (FNAC) and FNAC findings are reported according to Bethesda classification. Bethesda categories are used for determining risk of malignancy. Data regarding sonographic classification of thyroid nodule and its cytological association with respect to final histopathological diagnosis remains scarcely available in India. Aims and Objective: The study evaluated euthyroid nodules for risk of malignancy and compared sonographic features and FNAC (Bethesda classification) findings with histopathology of excised samples. Material and Methods: This was a single-center observational study on 137 consecutive subjects of solitary euthyroid nodule. All subjects underwent USG according to TIRADS and FNAC where applicable. Surgical biopsy report was used as a gold standard. Results: The sensitivity, specificity, accuracy, positive predictive and negative predictive value of FNAC were 80%, 90%, 85%, 86%, and 86.6% and TIRADS were 80%, 47.2% 61%, 51.3%, and 77.3%, respectively. FNAC classification was equally sensitive and more specific than TIRADS. Among individual USG parameters, micro-calcification was most sensitive (80%) and specific (86%). Irregular margin and taller-than-wider shape had a specificity of 89% and 92%, respectively. 3 patients (14.28%) with benign cytology and suspicious USG features (specifically TIRADS 4 & 5) undergoing surgery had malignancy in final HPE. Conclusions: USG and FNAC are equally sensitive in diagnosing malignant thyroid nodule but FNA is more specific (90%). It's a minimally invasive method which can be used to distinguish malignant from benign lesions with a high degree of accuracy (85%). In patient having high risk feature on USG, a benign cytology needs to be repeat FNAC and they should undergo surgical biopsy for confirmation.